Correlation of Stone Size and Urine Leukocytes in Nephrolithiasis Patients at Ulin General Hospital Banjarmasin - Noorsyifa Safitri Tahir; Eka Yudha Rahman; Dewi Indah Noviana Pratiwi; Heru Prasetya; Siti Kaidah (Fakultas Kedokteran Universitas Lambung Mangkurat, 2021)
Abstract: Nephrolithiasis (Kidney Stone) is a condition where there is stone in the kidney that are formed due to disturbance of the balance between solubility and deposition of salt in urine. This study was aim to determine the correlation between stone size and urine leukocytes in nephrolithiasis patients. This study was conducted at the Ulin General Hospital in Banjarmasin by taking data on medical records for the 2017-2018 period. This study used a cross-sectional retrospective approach with an analytic method. Samples were obtained using total sampling technique based on inclusion and exclusion criteria. A total of 34 nephrolithiasis patients were obtained that met the inclusion and exclusion criteria. The highest proportion of stone size was >20 mm (47.07%). The highest proportion of urine leukocytes was +3 (38.23%). Data were analyzed using the Spearman correlation test and showed p = 0.774 and r = 0.051. There was no significant correlation between stone size and urine leukocytes in nephrolithiasis patients at Ulin General Hospital Banjarmasin. Keywords: Nephrolithiasis, kidney stone size, urine leukocytes.